2013
DOI: 10.1111/liv.12264
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylation of long interspersed nuclear element‐1 promoter is associated with poor outcomes for curative resected hepatocellular carcinoma

Abstract: BackgroundEpigenetic alterations are well documented in hepatocarcinogenesis. However, hypomethylation of long interspersed nuclear element 1(LINE-1) promoter and its relationship with clinicopathological features in hepatocellular carcinoma (HCC) remain unknown.MethodsThe bisulfite-specific PCR and DNA sequencing analysis was performed to assess the methylation status of LINE-1 promoter in a pilot cohort of 71 patients with HCC. Additionally, methylation levels of two hot CpG sites of LINE-1 promoter, site 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 38 publications
3
33
1
Order By: Relevance
“…However, the significant difference between adjacent non-tumor tissues and normal liver tissues was not observed in this study, and hypermethylation of TRIM58 appeared in HCC tissues, but not in adjacent non-tumor tissues and normal liver tissues. The results indicated that hypermethylation of TRIM58 (>10%) was one of the specific events associated with tumorigenesis rather than other benign pathological processes, such as inflammation and cirrhosis (18).…”
Section: Discussionmentioning
confidence: 94%
“…However, the significant difference between adjacent non-tumor tissues and normal liver tissues was not observed in this study, and hypermethylation of TRIM58 appeared in HCC tissues, but not in adjacent non-tumor tissues and normal liver tissues. The results indicated that hypermethylation of TRIM58 (>10%) was one of the specific events associated with tumorigenesis rather than other benign pathological processes, such as inflammation and cirrhosis (18).…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, stepwise progression of methylation alterations may take place during the development of HCC. Many studies have reported that DNA hypomethylation in tumors is associated with aggressive tumors showing rapid growth [16,17]. We previously reported that the number of genes with hypermethylation increased with tumor progression [18].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that a hypomethylation of the CpG site of LINE-1 at the promoter region, particularly at CpG site seven, which is the number 172 nucleotide of LINE-1 promoter (gene bank: X58075), is associated with the LINE-1 re-expression [27]. Therefore, the results of methylation specific polymerase chain reaction (PCR) (MSP), which detects specific methylation status at this CpG site, would indirectly indicate the expression status of the LINE-1 gene in a tested sample.…”
Section: Dna Methylation Analysismentioning
confidence: 99%